Trapped by Evil and Deceit The Story of Hansi and Joel Brand. - Brand, Daniel (Academic Studies Press, 2021)
Trapped by Evil and Deceit is a historical account of true events that reads like a political thriller. Amazingly, a few Jews successfully saved thousands of lives during the holocaust. After barely surviving, they were ostracized and even murdered in Israel to conceal the inaction of the political elite.